Tuning Photodynamic Properties of BODIPY Dyes, Porphyrins' Little Sisters - Krzemien, Wojciech; Rohlickova, Monika; Machacek, Miloslav; Novakova, Veronika; Piskorz, Jaroslaw; Zimcik, Petr (Molecules (Basel, Switzerland), 2021)
The photodynamic properties of a series of non-halogenated, dibrominated and diiodinated BODIPYs with a phthalimido or amino end modification on the phenoxypentyl and phenoxyoctyl linker in the meso position were investigated. Halogen substitution substantially increased the singlet oxygen production based on the heavy atom effect. This increase was accompanied by a higher photodynamic activity against skin melanoma cancer cells SK-MEL-28, with the best compound reaching an EC50 = 0.052 ± 0.01 µM upon light activation. The dark toxicity (toxicity without light activation) of all studied dyes was not detected up to the solubility limit in cell culture medium (10 µM). All studied BODIPY derivatives were predominantly found in adiposomes (lipid droplets) with further lower signals colocalized in either endolysosomal vesicles or the endoplasmic reticulum. A detailed investigation of cell death indicated that the compounds act primarily through the induction of apoptosis. In conclusion, halogenation in the 2,6 position of BODIPY dyes is crucial for the efficient photodynamic activity of these photosensitizers.
Keywords: BODIPY; fluorescence; photodynamic therapy; singlet oxygen; heavy atom effect